Optimized Design of New 24-pulse Rectifier - Mu, Wenbin; Wu, Hao (International Journal of Electric Power and Energy Studies, 2024)
Compared with the conventional 24-pulse rectifier, the low-voltage winding of the rectifier transformer must be connected in the y and d modes, so that the voltage phase of the low-voltage side of the transformer is separated by 30° in sequence. This paper uses the phasor method to obtain a set of phase voltages that move towards 15° through the equivalent of three-phase voltages, so that the two sets of voltages produce a phase difference. Then, through decoupling and voltage reduction, the electrical quantity is converted into a signal quantity, the voltage level is reduced, and then the electrical quantity output is obtained to obtain the required voltage value. Finally, the required DC power is obtained through the rectification system. The effectiveness of the reverse model of this paper is verified by comparing the results and efficiency with the conventional 24-pulse rectifier.